Primiparous women with confirmed delay in labour: incidence and outcomes. (18th April 2012) - Kenyon, S; Johnston, T; Howman, A; Cheed, V; Walkinshaw, S; Waugh, J
Abstract : Introduction: Evidence suggests that the WHO partogram action line based diagnosis of delay is seen in 40% of spontaneously labouring primigravid women, with an overall CS rate of 9%.1 In 2007 NICE Intrapartum Guideline2 suggested modification to the diagnosis of confirmed delay in the 1 st stage of labour taking account of all features of progress and a 2-hour period of suspected delay. Evidence suggested this change would reduce intervention without harm. We present data from a pilot trial of high (4 mu/minute) v standard (2 mu/minute) oxytocin augmentation for delay in the first stage of labour diagnosed using strict NICE criteria. Methods: Audit data on incidence of suspected and confirmed delay (from electronic systems and notes) and data on maternal and perinatal outcomes for those recruited were collected. Results: The incidence of suspected delay was 11% and of confirmed delay 7%: a third of women made progress in the 2-hour interval. 94 women were recruited from three sites between November 2010 and May 2011. Their mode of birth was spontaneous vaginal birth 23%, instrumental vaginal birth 40%, caesarean birth 34%, 2% withdrew. There were 2 3 rd degree tears and 2 cases of blood loss >1000ml. No infant had a cord artery pH <7.05 or 5-minute Apgar score <7. Conclusion: Implementation of NICE Guidance for suspected / confirmed delay appears to reduce the incidence of 'delay in labour' and hence the overall CS rate. Women with confirmed delay have a high operative birth rate but no significant neonatal morbidity.